2002
DOI: 10.1080/00150190215116
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties of Bi 12 SiO 20 Crystals Doped by Cr and Mn Ions

Abstract: Frequency-temperature characteristics of dielectric permittivity and loss factor of Bi 12 SiO 20 crystals doped by Cr and Mn ions have been carried out in audio frequency range in temperature interval 290 to 800 K. Dielectric anomalies of relaxation (Bi 12 SiO 20 :Cr) and resonance (Bi 12 SiO 20 :Mn) types and Cole-Cole dependences close to linear ones have been observed. The results are discussed on the basis of "screened hopping" model. Photorefractive crystals Bi 12 MO 20 (BMO, where M = Si, Ge, Ti) possess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…One has to take into consideration intense temperature quenching of the PL of the type I [1] and temperature activation of the intrinsic photoconductivity with increasing temperature up to 300 K [3], on the one hand, and increase in the intensity of this PL and temperature quenching of the photoconductivity of BSO at Т ≤ 80 K (see Fig. 1c, curves 1 and 2), on the other hand.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One has to take into consideration intense temperature quenching of the PL of the type I [1] and temperature activation of the intrinsic photoconductivity with increasing temperature up to 300 K [3], on the one hand, and increase in the intensity of this PL and temperature quenching of the photoconductivity of BSO at Т ≤ 80 K (see Fig. 1c, curves 1 and 2), on the other hand.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, the existence of deep levels, with the energy of optical activation Е а О ≈ 2.6-3.0 eV, has been evidenced by spectral studies of the photoconductivity and the optical absorption in BSO. These levels are responsible for electron generation, providing a high 'extrinsic' photoconductivity and a 'shoulder' of the absorption profile near the fundamental absorption edge in BSO [3][4][5]. Magneto-optical and PCE studies have revealed that the intra-centre transitions taking place in the Bi-O complexes also contribute to the absorption shoulder [4,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation